Designing infrared travelling-wave antennas for environmental sensing - Priyadarshni Manivannan (Nanyang Technological University, 2020)
Environmental sensing of hazardous gases has been a pressing issue in the world, given the danger of accidentally being exposed to such harmful gases that might cause serious health problem or even death in extreme cases. Current environmental sensors focus on large-scale sensing such address global warming, which leaves a gap in the market for a smaller scale yet equally important environmental sensor with the ability to detect all hazardous gases in the air using an antenna. Antennas are all around us andhave been used for receiving and transmitting information all around the world. Theyare of different sizesandvary fromvery large structures like satellite dishes tovery smallsuchas micro-or nano-antennas that can fit in devices such as our mobile phones. Such miniaturized nano-antennas has allowed manipulation of infrared energy, which was previously inaccessible, with the help of special synthetic customizable materials known as “metamaterials”. This project researches on an appropriate metamaterial configurationfor the antenna, dependence of frequency splitting on strength of target scatterer and how to steer the system into exceptional point. Then, the perturbation strength of a target scatterer is calculated using MATLABand finally, COMSOL simulation software is used to simulate the cross section of such a nano-antenna that is able to detect changes in the gas molecules in the air. This research would pave way to the future production of such travelling-wave antennas to be used as gas sensorsto detect hazardous gases in the environment.